Manajemen Dakwah Bil Lisan Perspektif Hadits - Rofiq Hidayat (Fakultas Dakwah IAIN Jember, 2019)
In this paper, the author presents a study of management of da’wah bil lisan (invitation to Islam through oral preaching) from the perspective of hadith (records or sayings of Prophet Muhammad PBUH). The current study discussed about how the concept of da’wah management was based on the hadiths of the Prophet in which the author intended to explore the relation of the hadiths to expert theories in management. This paper presented the definition of Da’wah management as well as the kinds of media employed. In addition, it also explained the concept of management of Da’wah in the form of planning, implementation, and evaluation. The results of the study revealed that: (1) Planning, Rasulullah (The Prophet) recommended preachers to develop a strategy of da'wah to make it easier and more appealing for the target of preaching so they wouldn’t leave. (2) Implementation, Rasulullah encouraged Da'I (a preacher) to avoid using false information (hoax), hate speech and boastful statements in delivering his preaches. (3) Evaluation, Rasulullah also encouraged us to self-evaluate for anything we had done and to control our desires.